NAFTA : setting the record straight. - LUSTIG, Nora C. (1997)
Argues that Nafta was not a cause of Mexico's 1995 financial crisis, and is infact contributing to Mexico's recovery. Also, employment losses caused to American workers by Nafta have been small despite the large rise in the US-Mexican wage gap caused by the peso crisis. Observes that the US and Mexico must contribute to the fulfillment and consolidation of the objectives set out in Nafta, and need to deter the influence of powerful lobbies which may conspire against Nafta's full implementation.